Association of 5-HTR2A -1438A/G polymorphism with anorexia nervosa and bulimia nervosa: A meta-analysis. (11th June 2021) - Yan, Pan; Gao, Bing; Wang, Shuqi; Wang, Shengdong; Li, Jing; Song, Mingfen
Highlights: We performed a meta-analysis on the association of 5-HTR2A -1438A/G polymorphism with susceptibility to AN and BN. The results suggested that -1438A/G polymorphism was associated with the risk of AN in Caucasians, but not in Asians. No association was found between -1438A/G polymorphism and the risk of BN either in overall or in Caucasian population. Abstract: Although a number of studies have been conducted on the association of -1438A/G polymorphism in serotonin 2A receptor (5-HTR2A) gene with anorexia nervosa (AN) and bulimia nervosa (BN), the results remained inconsistent. We thus performed a meta-analysis to clarify the effects of -1438A/G polymorphism on the risk of AN and BN. PubMed, Embase, the Cochrane Library, CNKI, Weipu and Wanfang databases were searched for eligible studies. Pooled odds ratio (OR) and 95 % confidence interval (CI) were calculated to estimate the strength of the association. Subgroup analysis was also performed by ethnicity. In total, 17 studies were included for the meta-analysis, of which 15 studies containing 2028 cases and 2725 controls were used for AN analysis and 7 studies containing 505 cases and 1129 controls for BN analysis. The results showed -1438A/G polymorphism was significantly associated with the risk of AN in four genetic models (allele model, A vs. G: OR = 1.31, 95 % CI = 1.11−1.64, P = 0.003; recessive model, AA vs. GA + GG: OR = 1.69, 95 % CI = 1.28−2.23, P = 0.000; dominant model, AA + GA vs. GG: OR = 1.35, 95 % CI = 1.02−1.79, P = 0.037; co-dominant model, AA vs. GG: OR = 1.94, 95 % CI = 1.29−2.92, P = 0.002) in Caucasians, but not in Asians. We failed to observe a significant association between -1438A/G polymorphism and the risk of BN either in overall or in Caucasian population. The present meta-analysis indicated that A allele and AA genotype of 5-HTR2A -1438A/G polymorphism may contribute to higher risk of AN, especially in Caucasians. However, this polymorphism was not associated with the susceptibility to BN.